Pengaruh Kerjasama Tim Dan Beban Kerja Terhadap Kinerja Pegawai Dinas Perindustrian Dan Perdagangan Provinsi Banten (International Forum of Researchers and Lecturers, 2025)
This research aims to: find out how much teamwork influences employee performance; to find out how much workload affects employee performance; to find out how much influence teamwork and workload have on employee performance. This research is quantitative research and was conducted at the Banten Province Department of Industry and Trade with a total of 60 respondents using purposive sampling. This research data was taken using questionnaires, observations, interviews. The analysis technique used in testing the hypothesis is a simple and multiple linear regression analysis technique with the help of SPSS 21. From the results of this test it can be concluded that the teamwork variable (X1) has a significant positive effect on employee performance (Y); the workload variable (X2) has a positive but not significant effect on employee performance (Y); the teamwork variable (X1) workload (X2) has a significant positive effect on employee performance (Y).